2007
DOI: 10.2134/jeq2006.0186
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Shallow Groundwater Nitrate in a Poorly Drained Riparian Area and Adjacent Cropland

Abstract: Riparian ecosystems, through their unique position in the agricultural landscape and ability to influence nutrient cycles, can potentially reduce NO3 loading to surface and ground waters. The purpose of this study was to determine the fate of NO3 in shallow groundwater moving along a lateral flowpath from a grass seed cropping system through an undisturbed mixed‐species herbaceous riparian area. Soil A (30–45 cm) and C horizon (135–150 cm) NO3, dissolved oxygen, and nitrous oxide concentrations were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 40 publications
1
25
1
1
Order By: Relevance
“…Our data for the Calapooia River did show a strong seasonal trend, where NO 3 − concentrations increased in November when seasonal precipitation began and then decreased from December through the summer. Th is fl ush of NO 3 − in the fall has been documented in groundwater and surface water at the poorly drained Lake Creek site and was associated with movement of N that was mineralized during the warm dry summer when the majority of surrounding perennial grass seed crops were seasonally dormant (Davis et al, 2007;Wigington et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data for the Calapooia River did show a strong seasonal trend, where NO 3 − concentrations increased in November when seasonal precipitation began and then decreased from December through the summer. Th is fl ush of NO 3 − in the fall has been documented in groundwater and surface water at the poorly drained Lake Creek site and was associated with movement of N that was mineralized during the warm dry summer when the majority of surrounding perennial grass seed crops were seasonally dormant (Davis et al, 2007;Wigington et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The hydrogeology of the Calapooia River basin of the southern Willamette Valley is very complex and includes a wide range of soils and drainage classes. On one tributary of the Calapooia River, water tables, poorly drained soils, and lateral flow of groundwater through the riparian soil created the classic scenario for maximum riparian NO 3 − removal (Davis et al, 2007; Davis et al, 2008; Griffith et al, 1997). Although this riparian soil was biologically active and capable of NO 3 − removal, Wigington et al (2003, 2005) showed that the majority of streamflow at this site came directly from saturated overland flow.…”
mentioning
confidence: 99%
“…The spatial and temporal dynamics of groundwaterlevel position have been shown to control vegetation composition and nutrient processing in riparian corridors [Burt et al, 2002;Hefting et al, 2004;Leyer, 2005]. Groundwater wells within floodplain areas can provide information regarding ecosystem hydrological and biogeochemical processes [Peterjohn and Correll, 1984;Smith et al, 1991;Brunke and Gonser, 1997;Morrice et al, 1997;Sjodin et al, 2001;Schilling et al, 2004Schilling et al, , 2006Davis et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Ground water nitrate inputs can potentially be reduced by 70 to 100% in riparian buffers (Peterjohn and Correll 1984, Lowrance et al 1984, Jacobs and Gilliam 1985, Osborne and Kovacic 1993, Hill 1996, Martin et al 1999). These reductions have been attributed to both denitrification and plant assimilation (Lowrance 1992, Haycock and Pinay 1993, Vought et al 1994, Verchot et al 1997, Kuusemets et al 2001, Dhondt et al 2002, Davis et al 2007, although it is difficult to distinguish between these two mechanisms in areas of shallow ground water that flows through soil with many roots, relatively high levels of organic matter and labile carbon (Hill 1996, Gold et al 2001.…”
mentioning
confidence: 99%